Sistem Pendukung Keputusan Menggunakan Metode MABAC Dalam Sistem Informasi Bedah Rumah - Meilina, Indah; Kurniawan, Rakhmat (Forum Kerjasama Pendidikan Tinggi (FKPT), 2024)
The BAZNAS social institution has various programs, one of which is a humanitarian program which includes house renovation assistance. Based on data from BAZNAS, this program was only formed and began to be realized in 2020. Currently, the determination of aid recipients/mustahiq is carried out through subjective assessments. The process of assessing potential aid recipients is still done manually, resulting in problems, namely houses that should not be entitled to aid are found and it takes a long time to determine the recipients of house renovations. This research aims to develop a Decision Support System using the MABAC Method in the Home Surgery Information System in Sigama Village. To make it easier for village officials to determine recipients of house renovation assistance, a web-based Decision Support System (SPK) has been developed. This research concludes that by applying the MABAC method, this system can help villages determine the highest ranking of each available option. Based on calculations using 5 alternatives and 5 criteria, the results show that Alternative 4 in the name of Sahdoni Siregar with a value of 0.343 is the best and is recommended for receiving house renovation assistance in Sigama Village.